Medial plantar-to-radial amplitude ratio: does it have electrodiagnostic utility in distal sensory polyneuropathy?. (3rd April 2017) - Kahraman Koytak, Pinar; Alibas, Hande; Omercikoglu Ozden, Hatice; Tanridag, Tulin; Uluc, Kayihan
Abstract : Purpose of the study : We proposed a new electrophysiological parameter medial plantar (MP)-to-radial amplitude ratio (MPRAR), similar to sural-to-radial amplitude ratio (SRAR), in the diagnosis of distal sensory polyneuropathy (DSP), based on the concept that distal nerves are affected more and earlier than proximal nerves in axonal neuropathies. We aimed to investigate the diagnostic sensitivity of this parameter in diabetic DSP, together with sensitivities of SRAR and MP nerve action potential (NAP) amplitude. Materials and Methods : In 124 healthy controls and 87 diabetic patients with clinically defined DSP and normal sural responses, we prospectively performed sensory nerve conduction studies (NCS), and evaluated the MP NAP amplitude, MPRAR and SRAR values. We determined the lower limits of normal (LLN) of these parameters in the healthy controls and calculated their sensitivities and specificities in detecting DSP in diabetic patients. Results : MP nerve amplitude and MPRAR values were significantly lower in the patient group, compared to controls. However, SRAR values did not differ significantly between the two groups. The LLN of MP NAP amplitude was found to be 4.1 μV. The cutoff values for SRAR and MPRAR were determined as 0.24 and 0.16, respectively. MPRAR was abnormal in 21.8% of patients. However, the most sensitive parameter in detection of DSP was MP NAP amplitude, which showed a sensitivity of 31% and a specificity of 100%. Conclusions : Although MPRAR is more sensitive than SRAR in detecting DSP, it does not provide additional diagnostic yield to the assessment of MP NCS alone in diabetic DSP patients with normal sural responses.